Sexual ethics an anthology - Hopkins, Patrick D. (Blackwell philosophy anthologies, 2023)
"Sexual Ethics: An Anthology is an accessible and provocative collection of readings on conceptual, ethical, and policy issues about sex. Designed for students, teachers, and anyone interested in exploring one of the major moral topics of our times, this collection avoids jargon and obscurity in favor of clear, straightforward discussion, covering a wide array of cases from all sides. It is intended to provoke thought, generate discussion, and analytically clarify the definitions, arguments, assumptions, and options of our personal, public, and political treatment of sex"--